Pengaruh Pemanfaatan Teknologi Informasi, Dukungan Manajemen Puncak Dan Kemampuan Teknik Pemakai Sistem Informasi Akuntansi Terhadap Kinerja Individu Pada Karyawan LPD Di Kabupaten Badung - Ni Putu Novi Ayu Antari; Ni Wayan Yuniasih; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2023)
The purpose of this study is to investigate the connection between the usage of information technology, managerial support, and technical abilities of information system users and individual performance. This study's population consisted of 240 Badung Regency Local Police Department (LPD) employees. Multiple linear regression, the coefficient of determination, the F test, and the t-test are employed for data analysis in this study. The outcomes of the study reveal that the usage of information technology has a positive and statistically significant influence on individual performance, that managerial assistance positively affects individual performance, and that personal technical ability positively affects individual performance.